Development of Mixed‐Cation CsxRb1–xPbX3 Perovskite Quantum Dots and Their Full‐Color Film with High Stability and Wide Color Gamut. Issue 15 (16th May 2018) - Baek, Seungmin; Kim, Sunghoon; Noh, Jae Young; Heo, Jin Hyuck; Im, Sang Hyuk; Hong, Ki‐Ha; Kim, Sang‐Wook
Abstract: Mixed‐cation Cs x Rb1– x PbX3 (X = Cl, Br, I) perovskite quantum dots (PeQDs) are developed and show high quantum yields of 93% and 86% for green and blue wavelengths, respectively. The stability is significantly improved under heat, UV, and water aging conditions. These improved properties are explained by the increased defect formation resistance and exciton binding energy with Rb incorporation. Perovskite films are fabricated using Cs x Rb1– x PbX3 PeQDs and cyclic olefin copolymer. The films have a wide color gamut covering up to 104.15% of the BT.2020‐defined color space, with the white light color coordinates of (0.33, 0.32), luminance of 68.86 Cd m −2, and correlated color temperature of 5299 K at 20 mA. Abstract : Mixed‐cation Cs x Rb1– x PbX3 (X = Cl, Br, I) perovskite quantum dots are developed and show high quantum yields of 93% and 86% for green and blue wavelengths. The stability is significantly improved under heat, ultraviolet, and water aging conditions. Their films have a wide color gamut covering up to 104.15% of the BT.2020‐defined color space.